ANALISIS PENGEMBANGAN KAPASITAS (CAPACITY BUILDING) PEGAWAI PADA BADAN KEPEGAWAIAN DAERAH KABUPATEN KENDAL - Dina Nurwira Endarsari; Ida Hayu Dwimawanti; Dewi Rostyaningsih (Journal of Public Policy and Management Review, 2014)
Regional Employment Board, not free from bureaucracy problems especially a problem in the development of capacity. The main problem is the problem of low participation of Training, lack of openness of information about training, lack of professional services, and so forth. Focus to be studied is the development of quality and employee career development. From the analysis of the results showed that the quality of human resource development is not too much encountered many obstacles. While in the employee career development, the main problem of the capacity building is no regulation about competency system for the promotion and establishment of Training. Therefore, we need a regulation of competence and reward and punishment system in both of the employee quality and career development.